User-centered development of video telephony for servicing mainly older users: Review and evaluation of an approach applied for 10 years - Väyrynen, Seppo; Röning, Juha; Alakärppä, Ismo (Human Technology, 2006)
A research and development (R&D) approach has been applied to video telephony (VT) in northern Finland since 1994 by broad consortia. The focus has been on the considerable involvement of ergonomics within the engineering and implementation of VT. This multidisciplinary participatory ergonomic R&D approach (PERDA) is described briefly, in general and through two cases. The user-centeredness should be discernible in this sociotechnical systemic entity. A consortium—comprising mainly manufacturers, individual and organizational users of technological products, and R&D organizations—serves as a natural context for product development. VT has been considered to have much potential for enhancing (multimedia) interaction and effective multimodal communication, thereby facilitating many activities of everyday life and work. An assessment of the VT system, called HomeHelper, involved older citizens, as clients or customers, and the staff of social, health, and other services.